POWERbreathe® S-Index Test - guidelines and recommendations for practitioners - Kowalski, T.; Klusiewic, A. (Biomedical Human Kinetics, 2023)
Study aim: POWERbreathe® S-Index Test is an accessible and functional evaluation of inspiratory muscle strength. The mainpurpose of this study is to present guidelines that allow to successfully apply the test in sports settings with high accuracy, robustness, and repeatability.